Measles outbreak in a French Roma community in the Provence-Alpes-Côte d'Azur region, France, May to July 2017. (November 2018) - Godefroy, Raphael; Chaud, Pascal; Ninove, Laetitia; Dina, Julia; Decoppet, Anne; Casha, Paul; Hraiech, Sami; Brouqui, Philippe; Cassir, Nadim
Abstract: Objectives: To analyse a measles outbreak in a Roma community. Methods: We describe a community-wide outbreak of genotype D8 measles that took place in southeastern France, between May and July 2017, along with the control measures adopted. Results: We identified a total of eighteen cases, between six months and 24 years old. All cases were unvaccinated or incompletely vaccinated and belonged to a sedentary French Roma community. Most of them (67%) were hospitalised, with three cases (17%) of severe measles including one death of a 16-year-old girl who had previously received oral corticosteroids. The latter was the only lethal case notified in France during the year 2017. Control measures included intensification of surveillance, isolation of cases, and a large vaccination campaign in this Roma community. During the outbreak period, there was no case of healthcare-associated measles transmission. A broad adherence to vaccination through the mediating role of both the chief of the community and the pastor allowed reaching completed vaccination coverage of 90%. Conclusions: Efforts should be concentrated to enhance access to health services for minorities such as the Roma community characterized by low vaccination coverage. A trustful relationship with leaders of the community is essential to ensure adherence to vaccination. In France, attributable mortality to measles is low and concerns mainly unvaccinated and immunodepressed patients.